A 12-month follow-up of hypopigmentation after laser hair removal - Fontana, Carla Raquel [UNESP]; Bonini, Daniel; Bagnato, Vanderlei Salvador (Taylor & Francis, 2013)
Introduction: Laser hair removal is becoming an increasingly popular alternative to traditional methods such as shaving, waxing, among other methods. Semiconductor diode lasers are considered the most efficient light sources available and are especially well suited for clinical applications including hair reduction. The effectiveness of laser hair reduction depends on many variables, including the skin type of the patient. Material and Methods: A patient with Fitzpatrick Skin Type IV was submitted to laser hair removal of the arms with a high-power diode laser system with long pulses with a wavelength of 800 nm, a fluence of 40 J/cm2 and a pulse width of 20 ms. A 12-month follow-up assessment was performed and included photography and questionnaire. Results: Hypopigmentation was observed after a single laser hair removal section. After 6 months with the area totally covered, a gradual suntan with a sun screen lotion with an SPF of 15 was prescribed by the dermatologist. After 12 months of the initial treatment, a complete recovery of the hypopigmentation was achieved. Conclusion: Although a safe procedure, lasers for hair removal may be associated with adverse side effects including undesired pigment alterations. Before starting a laser hair removal treatment, patients seeking the eradication of hair should be informed that temporary, and possibly permanent, pigmentary changes may occur. © 2013 Informa UK, Ltd.
Keywords: Damage; Hair removal; Laser; Pigmentation; Skin; sunscreen; adult; case report; dermatologist; diode laser; esthetic surgery; female; follow up; human; hypopigmentation; low level laser therapy; photography; priority journal; pulse wave; questionnaire; skin; suntan